Effect of institutional transcatheter aortic valve replacement volume on mortality: A systematic review and meta‐analysis. Issue 3 (10th February 2021) - Kir, Devika; Shapero, Kayle; Chatterjee, Saurav; Grimshaw, Alyssa; Oddleifson, August; Spatz, Erica S.; Goldsweig, Andrew M.; Desai, Nihar R.
Abstract: Objective: We sought to conduct a systematic review and network meta‐analysis to examine the association between institutional transcatheter aortic valve replacement (TAVR) volume and all‐cause mortality. Background: Since inception in 2011, there has been an exponential increase in the number of TAVR centers across the world. Multiple studies have questioned if a relationship exists between institutional TAVR volume and patient outcomes. Methods: We performed a systematic literature search for relevant articles using a combination of free text terms in the title/abstract related to volume, TAVR, and patient outcomes . Two reviewers independently screened all titles/abstracts for eligibility based on pre‐specified criteria. All‐cause mortality data was pooled from eligible studies and centers were categorized as low‐(30–50 cases), intermediate‐, or high‐volume (75–130 cases) based on their annual TAVR volumes. Results: Our search yielded an initial list of 11, 153 citations, 120 full text studies were reviewed and 7 studies met all inclusion and exclusion criteria, yielding a total of 1, 93, 498 TAVRs. Categorized according to center's annual volume; 25, 062 TAVRs were performed in low‐, 77, 093 in intermediate‐ and 91, 343 in high‐volume centers. Network meta‐analysis showed a relative reduction in mortality rates of 37%, 23% and 19%, for high volume versus low volume centers, high volume versus intermediate volume centers and intermediate versus low volume centers, respectively. Conclusions: Existing research clearly shows an inverse relationship between annual TAVR procedural volume and all‐cause mortality. We need to focus on development of strong referral networks and consolidation rather than expansion of existing TAVR centers to improve patient outcomes, while ensuring adequate access‐to‐care.